Learning to listen, learning to teach : the power of dialogue in educating adults - Vella, Jane Kathryn, 1931- (San Francisco, CA : Jossey-Bass, 2002)
In this updated version of her landmark book, celebrated adult educator Jane Vella revisits her twelve principles of dialogue education with a new theoretical perspective gleaned from the discipline of quantum physics
Part one: a process that works and why. Twelve principles for effective adult learning -- Quantum thinking and dialogue education -- How the principles inform course design: two examples -- Part two: the principles in practice: across cultures and around the world. Learning needs and resources assessment: taking the first step in dialogue -- Safety: creating a safe environment for learning -- Sound relationships: using the power of friendship -- Sequence and reinforcement: supporting their learning -- Praxis: turning practice into action and reflection -- Learners as decision makers: harnessing the power of self through respect -- Learning with ideas, feelings, and actions: using the whole person -- Immediacy: teaching what is really useful to learners -- Assuming new roles for dialogue: embracing the death of the professor -- Teamwork: celebrating learning together -- Engagement: learning actively -- Accountability: knowing how they know they know -- Part three: becoming an effective teacher of adults. Reviewing the twelve principles and quantum thinking -- How do you know you know? Supposing and proposing -- Appendix: Ways of doing needs assessment
Includes bibliographical references (pages 251-254) and index
Keywords: Adult education; Adult learning; Teaching; Education; Education, Continuing; Learning; Psychology, Educational; Teaching; Adult